Decoding E-Experience in Educational Technology: The Mediating Role of E-Trust and E-Satisfaction in Continuance Intention - Ni Putu Nurwita Pratami Wijaya; Vanessa Gaffar; Bambang Widjajanta; Denny Andriana; Dwinto Martri Aji Buana (Online Learning In Educational Research (OLER), 2025)
The startup sector's emphasis on the educational technology industry in Indonesia expanded, particularly during the pandemic. However, many educational technology players went bankrupt because they could not make their users reuse their products and services (continuance intention). This study aimed to analyze the influence of e-experience on continuance intention in the use of educational technology platforms, with e-trust and e-satisfaction as mediating variables. A quantitative method with a PLS-SEM approach was used to test the relationships between variables. Data were gathered from 300 respondents using a questionnaire as the research instrument. The respondents in this study were individuals utilizing educational technology, including students, teachers, and employees seeking skill enhancement. The data were analyzed using SmartPLS. The research results showed that e-experience had a direct influence on continuance intention, but its impact was relatively small. E-trust and e-satisfaction proved to be significant mediators in strengthening this relationship. E-Satisfaction had a stronger mediating influence compared to e-trust, affirming that user satisfaction was a key factor in driving the sustainability of educational technology usage. Moreover, the indirect effects through mediators were greater than the direct effects, indicating that user experience should be developed into trust and satisfaction to enhance user retention.